Spatial versus temporal structure: Implications of inter‐haul variation and relatedness in the North‐east Atlantic spurdog Squalus acanthias. Issue 5 (2nd August 2018) - Thorburn, James; Jones, Rosie; Neat, Francis; Pinto, Cecilia; Bendall, Victoria; Hetherington, Stuart; Bailey, David Mark; Leslie, Noble; Jones, Cath
Abstract: Micropopulation processes, such as gene flow, operating within geographic regions are often poorly understood, despite their potential to affect stock structure and sustainability. This is especially true for highly mobile species, such as elasmobranchs, where the potential for spatial overlap of regional populations is increased as a result of greater movement capabilities. A lack of information on these processes means that management plans rarely consider spatio‐temporal structure. Spurdog ( Squalus acanthias ) are globally distributed throughout temperate regions yet there is an apparent lack of gene flow between ocean basins. In the North‐east Atlantic there is little work on gene flow within the region, which is currently managed as a single stock that is estimated to be at 19% compared with 1905. Some evidence from this region suggests population processes that have the potential to cause structuring. The population structure of the North‐east Atlantic spurdog was investigated using an 828‐bp fragment of the mitochondrial DNA control region and seven focal polymorphic microsatellite markers. Samples from 295 individuals from eight locations throughout UK waters were used in this study. Overall, mitochondrial sequences suggest some regional differentiation. Genetic diversity was comparable with that reported in previous studies of spurdog. Haplotype diversity (0.782–1.000) is amongst the highest observed for an elasmobranch. Microsatellite markers suggest that a high level of relatedness was responsible for regional population structuring. There was no apparent spatial structure after removal of 'full sibling' relationships. Inter‐haul variation from Celtic Sea samples is suggestive of subpopulations and aggregation events, which may have important implications for fisheries conservation of this and other elasmobranch species.